Hats Off to HIT: A Case Report - Akhwand Shakeel Ahmad (Oman Medical Journal, 2012)
Thrombocytopenia is a well- recognized complication of heparin therapy. The diagnosis is mostly clinical and the main value of laboratory testing is in excluding the diagnosis. We describe here a patient with stroke who had aspiration pneumonia leading to sepsis. She developed atrial fibrillation and received heparin which had to be stopped prematurely due to melena. Within 5 days of heparin, she had thrombocytopenia which was heparin-induced thrombocytopenia (HIT), but the diagnosis was missed initially as heparin was no longer on the drug chart.